The Effect of Group Cognitive Behavior Therapy on Behavior Changes on Adolescents Risked at Drug Abuse based on Age Characteristics in Kabupaten Dharmasraya - Wisdia Lola Erwinda; Susmiati Susmiati; Heppi Sasmita (NERS Jurnal Keperawatan, 2019)
Various problems in adolescents are increasing, one of which is the drug abuse. Considering the condition of Kab. Dharmasraya, which is very vulnerable to drug trafficking cases, a prevention act to drug abuse behavior among adolescents is required. This study aimed to determine the effect of Group Cognitive Behavior Therapy (GCBT) on behavior changes on adolescents risked at drug abuse in Kab. Dharmasraya. This study was a Quasi Experimental Research with Pretest and Posttest With Control Group. The samples were 64 people consisting of 32 people in the control group and 32 people in the intervention group. The results of this study indicated that there was a significant influence on changes in adolescent behavior in the intervention group. Meanwhile, there was no significant differences happened in the control group. Therefore, Group Cognitive Behavior Therapy (GCBT) can be applied to change the behavior of adolescents risked at drug abuse. It is expected that GCBT can be implemented at schools in collaboration with the health department to prevent drug abuse behavior on adolescents.